معالجة الإشارة اللّاسلكيّة في الأنظمة الخلويّة باستخدام المرشّح المتكيّف - عملة, ياسر; الرضوان, هيثم; جنيكه, فرح (Latakia University Journal -Engineering Sciences Series, 2019)
Wireless systems including cellular system suffer from many phenomenas associated with electromagnetic waves propagation such as interference, fading, multipaths propagation, Doppler deviation, etc…, in addition to the noise effect associated with the communication channel. Since the cellular system relies on frequency reuse to improve capacity and spectral efficiency, the effect of these phenomenas increase as time the traditional methods do not succeed to eliminate them completely, which calls for using advanced methods of signal processing in real time. Therefore, the study examines using the adaptive filter technology to cancel the the co- channel and adjacent channel interference, and shows its ability to improve the signal to interference ratio significantly. It also studies the additive white gaussian noise cancellation (AWGN), which simulates the random noise that changes instantaneously and affects the wireless signal as it travels in the radio medium, The study shows the difference between the working mechanism of the adaptive filter used for processing in both cases. The rest of the other phenomenas that are the radio signal exposed to it and methods of handle using adaptive filter will be studied in the next researchs. تعاني الأنظمة اللّاسلكيّة بما فيها النّظام الخلوي من العديد من الظّواهر المرافقة لانتشار الأمواج الكهرومغناطيسيّة مثل التّداخل، والخفوت، والانتشار متعدد المسارات، وانحراف دوبلر وغيرها..، بالإضافة إلى تأثير الضّجيج المرافق لقناة الاتصال، وبما أنّ النّظام الخلوي يعتمد على إعادة استخدام التّردد من أجل تحسين السّعة والفعاليّة الطيفيّة لذلك يزداد تأثير هذه الظّواهر في الوقت الذي لا تنجح فيه الطّرق التقليديّة في إلغاء تأثيرها بشكل كامل وهذا ما يدعو إلى استخدام طرق متقدّمة لمعالجة الإشارة في الزّمن الحقيقي. لذلك يتناول البحث استخدام تقنية المرشّح المتكيّف لإلغاء تداخل القناة المشابهة والقناة المجاورة ويظهر قدرته على تحسين نسبة الإشارة إلى التّداخل بشكل كبير، كما يدرس إلغاء الضّجيج الغوصي الأبيض المضاف الذي يحاكي الضّجيج العشوائي المتغيّر بشكل لحظي والمؤثر على الإشارة اللّاسلكيّة أثناء انتقالها في الوسط الرّاديوي، وتظهر الدّراسة الفرق في آلية عمل المرشّح المتكيّف المستخدم للمعالجة في كلا الحالتين، أمّا بقية الظواهر الأخرى التي تتعرض لها الإشارة اللّاسلكية وطرق معالجتها باستخدام التّرشيح المتكيّف فستدرس في الأبحاث القادمة.